Combining two main NAL1 functional alleles can increase rice yield - Ouyang, Xiang; Chang, Shuoqi; Ma, Xiaoling (Frontiers in Plant Science, 2024)
NARROW LEAF1 (NAL1) is one of the key genes in regulating photosynthesis and plant architecture simultaneously. As the antagonistic effects of NAL1 have concurrent impacts on photosynthesis and yield component traits, how we can effectively utilize the NAL1 gene to further increase rice yield is not clear. In this study, we used two main different functional NAL1 alleles each has been proven to own the specifically advantageous traits previously, and tested whether the combined NAL1 alleles have higher yield than the homozygous. Our results exhibited that the combined NAL1 alleles had better parent heterosis (BPH) on panicle number and total filled grain number per plant, and had middle parent heterosis (MPH) on spikelet number per panicle without affecting thousand grain weight when compared with the homozygous alleles. In consequence, the NAL1 hybrid plants displayed highly increased grain yield than both homozygous parents. The hybrid plants also showed a better plant architecture and higher canopy photosynthesis. Western blot and proteomics results showed the hybrid plants had a middle abundant NAL1 protein level, and the up-regulated proteins mainly involved in nucleus and DNA binding process but the down-regulated proteins mainly involved in oxidation-reduction process, single-organism metabolic process and fatty acid biosynthetic process. Furthermore, the hybrid vigor effect of NAL1 was confirmed by substituting the mutual male parent 9311 with 9311-NIL in two super hybrid rice varieties (LYP9 and YLY1). This study demonstrates that we can achieve a higher level of grain production in hybrid rice by using the heterosis of NAL1.